IMPLIKATUR PERCAKAPAN DALAM TUTURAN BERBAHASA INDONESIA PADA ACARA INI TALKSHOW NET TV - Bagus Tri Handoko (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2020)
This study aims to identify the conversational implicature contained in the TV Net Talk Show program. In this study, researchers sought (1) to describe violations of the principle of cooperation that led to the emergence of implicature, (2) to describe the form of acts of implication. The approach used in this research is descriptive qualitative. The data of this research is in the form of the speech of the NET TV Talk Show which aired in the March 2020 airing period. Data collection techniques used were the recording technique and the note-taking technique. The recording technique is done by downloading a video of this program. A NET TV Talk show that aired in March 2020. From the results of the data that has been studied, violations of the principle of cooperation that led to the emergence of conversational implicatures on this program Talkshow is dominated by violations of the maxim of quantity, in terms of speech acts the implications of the Talkshow program are dominated by the use of news sentences.